A Study of Factors Affecting The Screw Spacing of Spoilers in Hard Disk Drives for Productivity Increase Using Multiple Regression Analysis - Sirikasemsuk, Kittiwat; Kiatcharoenpol, Tossapol; Waiyaroop, Hanoof; Kullawong, Tadpon; Treeranurat, Laksiri (Naresuan University Engineering Journal, 2021)
A spoiler is a part of a hard disk drive that can reduce the airflow velocity and force at an actuator arm and its head. At a case study for a hard disk drive manufacturer, the main problem was that the spoiler was tightened too loosely in the hard disk drive by the spoiler installation machine, thereby gaining a defect. Its response could be measured by the screw spacing (also called ‘the screwdriver encoder’) for the spoiler installation in the hard disk drives. The purpose of this paper was to determine and analyze the factors affecting the screwdriver encoder by means of the multiple regression analysis. The mathematical model of the screwdriver encoder and its significant factors were suitably built. With data collected from the spoiler installation machine and its software, it was found that there were the following four potential factors which plausibly affected the screwdriver encoder: 1. the screw torque, 2. the bit angle, 3. the amount of time spent in tightening the screw, and 4. the vacuum level for picking the screw. From the ANOVA table, it was found that: 1. The screw torque (under the range of these experimental values) did not affect the screw spacing, 2. The amount of time had the largest effect on the screw spacing because its F-Value was more than the others, and 3. The optimal values for setting the spoiler installation machine were explored in this paper. Besides, this research considered the criteria for selection of the suitable model from the coefficient of determination (R2) and the mean square error (MSerror). In addition, the mean absolute deviation (MAD) was simultaneously considered.